OFFLINE TESTING OF MICRO-ELECTRODE-DOT-ARRAY DIGITAL MICROFLUIDIC BIOCHIPS USING DESIGN-FOR TESTABILITY - SHUKLA, VINEETA (2018)
Digital Microfluidics is a developing technology that manipulates small amount of liquids on a biochip. These biochips have enabled the automation of laboratory procedures and are used in various application areas including on-chip DNA analysis and point-of-care diagnosis.